Working with boards: The experiences of Australian managers in performing arts organisations. Issue 3 (4th June 2018) - Glow, Hilary; Parris, Melissa A.; Pyman, Amanda
Abstract: Corporate governance has long been a feature of the arts and cultural sector and is a requirement for all cultural organisations seeking public funding, regardless of their size. However, despite the ubiquity of corporate governance in the arts and cultural sector, there is little research addressing the experiences of managers. This study examines the experiences of managers in performing arts organisations in working with their boards, based on data collected across 20 performing arts organisations in Australia using a stakeholder salience lens. Our results indicate that while the board is seen as a key organisational stakeholder, managers have a range of concerns about the governance role of boards, and in particular their limited effectiveness on the dimensions of legitimacy and urgency. We find that arts managers often must wrestle with competing agendas around creative autonomy and the low‐risk appetite of their management boards. Our findings highlight the need to re‐align, particularly in small‐ and medium‐sized organisations, the organisational needs of arts managers with corporate governance arrangements, without detracting from creative endeavours. Abstract : The reported study examines the experiences of managers in performing arts organisations working with their boards using a stakeholder salience lens. Results indicate that while the board is seen as a key organisational stakeholder, managers have concerns about their governance role, perceiving boards to be limited in their effectiveness on the dimensions of legitimacy and urgency.